Pelatihan pengembangan emping beras sebagai produk unggulan di desa Jirak kecamatan Sajad - Ega Aprisa; Lusi Lestari; Aswitri Aswitri; Rosa Amelia; Nur Hikmah (Universitas Pendidikan Indonesia (UPI), 2021)
Jirak Village is one of the villages located in Sajad District, Sambas Regency, West Kalimantan Province. Jirak Village has a variety of agricultural and plantation products, including rice. Rice in Jirak Village is usually harvested every 2 times a year, so the amount of rice is abundant and easy to find. The rice commodity in Jirak Village has the potential as a raw material for superior products made from processed food in the form of rice chips which have high selling value. The purpose of this training is to improve and develop rice chips as a superior product of Jirak Village. The approach used in this activity includes a model of material exposure, discussion, practice and evaluation. This activity took place in March 2022. The number of participants who joined in this training was 11 people, of which 11 people were a group of PKK women who were members of Jirak Village. Based on this training activity, it was found that 36% of PKK mothers agreed and 64% strongly agreed to develop rice chips packaging with more practical sizes so as to make rice chips products as souvenirs typical of Jirak Village. This training also motivates the people in Jirak Village. The success of this training and mentoring can be illustrated by the results of the distribution analysis which shows the percentage of PKK mothers who agree with this activity. Other conditions also illustrate that this activity is fully supported by the village head, namely by lending the existing facilities and infrastructure in the village. It is hoped that in this training the community can develop rice chips into other new types of chips so that they are better known by the wider community and also have easily recognizable characteristics, especially from Jirak Village.